Anxiety status of junior archers in COVID-19 during training isolation period towards the shooting performance - Wan Nurlisa Wan Ahmad; Mohd Azrul Hisham Mohd Adib; Irdayanti Mat Nashir; Mon Redee Sut Txi; Fatin Nurfatehah Mat Salleh; Jing Rui Tang (International Journal of Public Health Science (IJPHS), 2023)
Studies have indicated that the COVID-19 pandemic has had miserable effects on athlete performance due to the movement control order (MCO) announced by the Malaysia Government. Dealing with self-training without the coach's guidance leads the archers to lose concentration, diminished self-confidence, and elevated anxiety levels. These factors contribute to inconsistent shooting performance. This study attempted to identify the archer's anxiety status during the training isolation period on the shooting performance. A total of 32 participants from the recurve archery category were recruited and enrolled in a web-based cross-sectional study during the MCO. The CSAI-2R instrument was applied to participants to examine the psychological aspect. Training Isolation resulted in a significant effect on anxiety status and shooting performance. Analysis from CSAI-2R, low-level archers, indicated 5% more anxiety than top-level archers for both cognitive and somatic anxiety sub-component. In contrast, Top archers revealed a higher self-confidence mean of 2.32 (moderately high) than low archers (1.38). The result shows improvement in anxiety and score performance with complete online monitoring and coaching supervision first session until the 8th session. These findings could assist sports institutions in improving a better training experience and understanding the pandemic's impact on athletes' mental health during home isolation.